Easy Access to HPC Resources through the Application GUI - Waveren, Matthijs van; Seif El Nawasany, Ahmed; Hassanein, Nasr; Moon, David; O’Byrnes, Niall; Clo, Alain; Murugan, Karthikeyan; Arena, Antonio (Supercomputing Frontiers and Innovations, 2016)
The computing environment at the King Abdullah University of Science and Technology (KAUST) is growing in size and complexity. KAUST hosts the tenth fastest supercomputer in the world (Shaheen II) and several HPC clusters. Researchers can be inhibited by the complexity, as they need to learn new languages and execute many tasks in order to access the HPC clusters and the supercomputer. In order to simplify the access, we have developed an interface between the applications and the clusters and supercomputer that automates the transfer of input data and job submission and also the retrieval of results to the researcher’s local workstation. The innovation is that the user now submits his jobs from within the application GUI on his workstation, and does not have to directly log into the clusters or supercomputer anymore. This article details the solution and its benefits to the researchers.